Salvia fimbriaticalyx, a new species of Salvia (Lamiaceae) from Oaxaca, Mexico - Fragoso-Martínez, Itzi; Martínez-Gordillo, Martha; Salas, Silvia (Phytotaxa, 2021)
In this study, we describe and illustrate Salvia fimbriaticalyx, a new species from Oaxaca, Mexico, which is morphologically similar to Salvia leptostachys, a species from section Angulatae. The new species differs from the latter by having persistent, lanceolate bracts with cuneate base; calyx lobes with a densely fimbriate margin; corolla tube longer (3–3.5 mm long), and the lower lip of the corolla shorter (3–3.5 mm long). Three molecular markers (ITS, trnL-trnF and trnH-psbA) were sequenced for the new species, and its phylogenetic position is discussed.